Studies on external genitalial morphology of subfamily Catocalinae (Lepidoptera: Noctuidae) - Ignacimuthu S; K, Sivasankaran; T, Babu Thangadurai (Journal of Research in Biology, 2011)
Genitalial morphology of fifteen species of the subfamily Catocalinae of Noctuidae was studied. The structure of uncus, saccus, valvae, Juxta and aedeagus of the male and corpus bursae, ductus bursae and signum of the female genitalia were analysed. The adult images, male and female genitalia were illustrated. A dichotomous key for the identification of species using genitalial structures is also presented.